Ethical Perspective of Biopedagogical Mediation - Castillo Cedeño, Ileana (2013)
This essay addresses the ethical perspective of biopedagogical mediation considering the importance of placing education in an alternative paradigm where both pedagogy and life complement each other to attend the freeing process of education. The main goal is to contribute to the meditation and action towards pedagogical mediation and its inherent bond to ethics. The article is based on the premise that there is a need to nourish principles and values that exalt life´s multidimesionality and complexity. Education, as a political proyect, has the challenge to prepare a planetary citizenship; a shared effort that brings every human being to work for a real mindful and social transformation in order to reach higher states of personal and social wellness. It is required to direct both energy and wisdom to visualize the, so demanded by the planet, human tranformation.